Parallels between contemporary western and Islamic thought on the discourse of power and knowledge - Mohd Yusof, Danial (Versita, Warsaw, 2012)
This paper examines parallels between contemporary Western and Islamic thought. It will propose that there is congruence between Western and Muslim political thought processes on issues of soft-foundationalism, negative theology, provisional truth claims and religious democracy, in order to offset hegemonic tendencies. This will be illustrated by a concise juxtaposition of the ideas of Davutoglu, Winkel, Sardar, Tariq Ali, Derrida, Foucault, Abdolkarim Soroush, Mohammed Arkoun and others. In the social sciences, namely political science, the neutralization of ideology is also supported in relation to the concern of ideological encroachments into the discipline by William E. Connolly, that echoes Karl Mannheim’s sociology of knowledge. This paper concludes that similar concerns on the relationship between power and knowledge in contemporary Western and Islamic political thought processes are beneficial to the study of Islam and its transformation as a social and political phenomenon.